Regioselective Hydrodebromination of Polybrominated Indoles. Issue 18 (30th April 2014) - Chelucci, Giorgio; Pinna, Gérard A.; Pinna, Giansalvo
Abstract: The mixture of sodium borohydride and N, N, N′, N′ ‐tetramethylethylenediamine in combination with a palladium catalyst is a mild and efficient system for the regioselective hydrodebromination of polybrominated indoles with both N ‐donating and N ‐withdrawing substituents [ N ‐methyl‐ and N ‐(methoxycarbonyl)indoles, respectively]. Abstract : The mixture of NaBH4 / N, N, N′, N′ ‐tetramethylethylenediamine in combination with a palladium catalyst is a mild and efficient system for the regioselective hydrodebromination of polybrominated indoles with both N ‐donating and N ‐withdrawing substituents [ N ‐methyl‐ and N ‐(methoxycarbonyl)indoles].